Petroleum Product Markets in Sub-Saharan Africa : Comparative Efficiency Analysis of 12 Countries - World Bank (Washington, DC, 2012)
Petroleum products are used across the entire economy in every country. Gasoline and diesel are the primary fuels used in road transport. Oil is used in power generation, accounting for eleven percent of total electricity generated in Africa in 2007. Adequate and reliable supply of transport services and electricity in turn are essential for economic development. Households use a variety of petroleum products: kerosene is used for lighting, cooking, and heating; liquefied petroleum gas for cooking and heating; and gasoline and diesel for private vehicles as well as captive power generation. Prices users pay for these petroleum products have macroeconomic and microeconomic consequences. At the macroeconomic level, oil price levels can affect the balance of payments, gross domestic product (GDP), and, where fuel prices are subsidized, government budgets, contingent liabilities, or both. At the microeconomic level, higher oil prices lower effective household income in three ways. First, households pay more for petroleum products they consume directly. Seventy percent of Sub-Saharan Africans are not yet connected to electricity; most without access rely on kerosene for lighting. Second, higher oil prices increase the prices of all other goods that have oil as an intermediate input. The most significant among them for the poor in low-income countries is food, on which the poor spend a disproportionately high share of total household expenditures. Food prices increase because of higher transport costs and higher prices of such inputs to agriculture as fertilizers and diesel used for operating tractors and irrigation pumps. For the urban poor that use public transport, higher transport costs also decrease their effective income. Third, to the extent that higher oil prices lower GDP growth, household income is reduced.